User acceptance of technology : a descriptive case study on JOBSMALAYSIA system in the context of Terengganu’s private employers / Yau’mee Hayati Mohamed Yusof, Sabiroh Md Sabri and Nurul Ulfa Abdul Aziz - Mohamed Yusof, Yau’mee Hayati; Md Sabri, Sabiroh; Abdul Aziz, Nurul Ulfa (2013)
In order to achieve the objective of this research, two research questions have been constructed. The research questions were constructed on theoretical considerations found in the literature review. Since the aim of this research is to explore the behaviour of the JOBSMALAYSIA system, the study is descriptive in its nature. The study primarily uses the Technology Acceptance Model (TAM) and The Unified Theory of Acceptance and Use of Technology (UTAUT) Model as theoretical basis. Both theories are widely used in information technology and information systems research to evaluate user acceptance of a system and to understand determinants of individual behaviour towards the system usage. ther Ordinal and nominal scale were applied to thirty two items. Out of 188 distributed questionnaire which used convenient sampling, only 57 usable responses were returned by the respondents among the private employers in Terengganu Darul Iman. The questionnaire were distributed by using postal, hand to hand delivery, faxes and also email. Detailed descriptive statistics which were related to the respondent's characteristics such as age, gender and experience are shown in Table 4.4, 4.5 and 4.6. Although the return rate of survey is only 30.3 %, but it has proved by prior research sample that use TAM or other user acceptance model shows that their response rates were also below 20%, similar to our case. The finding of this study reveals 48.81% respondents agreed with the usage of the system that shows positive acceptance towards the system.This is almost congruent with the finding that concluded by (Zulridah et all, 2011) saying that ELX score using their tools, ELXCSI is equal to 66 which considered as moderate but above average. The anxiety factor is chosen to be the most influence factor among the seven other factors . The employers in Terengganu Darul Iman are considered to be at average level of acceptance to use the system . This research should also be able to highlight and emphasize the importance of user involvement during the development of a new system especially as reference for the Government in the future.